In Vitro and In Vivo Evaluation of Targeted Sunitinib‐Loaded Polymer Microbubbles Against Proliferation of Renal Cell Carcinoma. (1st March 2016) - Hu, Jie; Zong, Yujin; Li, Jun; Zhou, Xiaodong; Zhang, Jun; Zhu, Ting; Jiao, Mingke; Su, Haili; Bo, Bin
Abstract : Objectives: The poor safety profile of sunitinib capsules has encouraged the identification of targeted drug delivery systems against renal cell carcinoma. This study aimed to explore the effect of sunitinib‐loaded microbubbles along with ultrasound (US) treatment on proliferation and apoptosis of human GRC‐1 granulocyte renal carcinoma cells in vitro and in vivo (xenograft tumor growth in nude mice). Methods: Liposomes containing sunitinib were prepared by using the transmembrane ammonium sulfate gradient method and then absorbed into polymer microbubbles to generate sunitinib‐loaded microbubbles. Entrapment of sunitinib was verified by 25‐25‐[ N ‐[(7‐nitro‐2‐1, 3‐benzoxadiazol‐4‐yl)methyl]amino]‐27‐norcholesterol staining. GRC‐1 cells were treated with microbubbles alone, liposomes alone, sunitinib alone, sunitinib‐loaded microbubbles without and with US, and no treatment (control). Cell survival and apoptosis were assessed at 12, 24, and 48 hours after treatment. Xenograft tumors were induced by implantation of GRC‐1 cells in nude mice. The animals with tumors were then randomly assigned to sunitinib alone, sunitinib‐loaded microbubbles − US, sunitinib‐loaded microbubbles + US, and no treatment (control; n = 10 per group). The tumor volumes were analyzed on the 7th, 15th, and 21st days. Results: The sunitinib entrapment efficiency in the liposomes was approximately 78%. The effective sunitinib concentration in each group was 0.1 μg/mL. The sunitinib‐loaded microbubble + US group showed a lower in vitro cell survival rate ( P < .001) compared with the other groups. Greater in vivo inhibition of xenograft tumor growth was also observed in the sunitinib‐loaded microbubble + US group compared with the other groups. Conclusions: Combined sunitinib‐loaded microbubbles and US treatment significantly inhibits growth of renal carcinoma cells both in vitro and in vivo.